The Effect of Attitudes, Subjective Norms, and Perceptions of Behavioral Control on Pregnancy Check-ups in Bojonegoro - Ulfah, Mariya; Anggraeni, Sri (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: In Indonesia, the use of antenatal care services has not been carried out according to standards. According to WHO, 99% of maternal deaths are due to the lack of information for pregnant women about the importance of regular prenatal check-ups. Objective: This study aims to examine the relationship strength between attitudes, subjective norms, and perceptions of behavioral control regarding antenatal care with the intention of pregnant women in conducting early pregnancy check-ups (K1) using a quantitative approach with a cross-sectional study design. Methods: The population in this study were 234 pregnant women who had their first antenatal contact with K1 at the Dander Health Center in Bojonegoro Regency, which was collected from March to August 2020. Probability sampling utilizing a basic random sample methodology was employed. Furthermore, 129 pregnant women were used as samples for this study. Data is collected in the form of primary data through a questionnaire, while the secondary data were analyzed using logistic regression. The dependent variable is the intention of pregnancy check-ups, while the independent variables are attitudes, subjective norms, and perceptions. Results: The results showed that there was a relationship between the attitude of pregnant women (p=0.001) and subjective norms (p=0.038) regarding pregnancy check-ups with the intention of pregnant women to visit K1 (α=0.05). However, there was no relationship between perceptions of behavioral control regarding antenatal care and the intention of pregnant women to visit K1 (p=0.142). Conclusion: The findings revealed an association between pregnant women's attitudes and subjective norms about prenatal care and their intention to attend K1. This study suggests that pregnant women's knowledge needs to be improved, including through classes about the importance of good subjective attitudes and norms related to antenatal care to support the intention to check pregnancy regularly especially K1 visits. As a result, early and regular pregnancy check-ups will detect high-risk pregnancies so that they can be handled immediately, thereby reducing maternal and infant mortality.